Manipulation of the crystalline phase diagram of hydrogen through nanoscale confinement effects in porous carbons. Issue 19 (6th May 2022) - Terry, Lui R.; Rols, Stephane; Tian, Mi; da Silva, Ivan; Bending, Simon J.; Ting, Valeska P.
Abstract : Confinement of H2 in subnanometre pores of microporous carbon stabilizes the lowest energy crystal confirmation at higher temperatures. Change in H2 phase behaviour shown to be caused by severe loss of rotational freedom and energy upon confinement. Abstract : Condensed phases of molecular hydrogen (H2 ) are highly desired for clean energy applications ranging from hydrogen storage to nuclear fusion and superconductive energy storage. However, in bulk hydrogen, such dense phases typically only form at exceedingly low temperatures or extremely high (typically hundreds of GPa) pressures. Here, confinement of H2 within nanoporous materials is shown to significantly manipulate the hydrogen phase diagram leading to preferential stabilization of unusual crystalline H2 phases. Using pressure and temperature-dependent neutron scattering at pressures between 200–2000 bar (0.02–0.2 GPa) and temperatures between 10–77 K to map out the phase diagram of H2 when confined inside both meso- and microporous carbons, we conclusively demonstrate the preferential stabilisation of face-centred cubic (FCC) solid ortho -H2 in microporous carbons, at temperatures five times higher than would be possible in bulk H2 . Through examination of nanoconfined H2 rotational dynamics, preferential adsorption and spin trapping of ortho -H2, as well as the loss of rotational energy and severe restriction of rotational degrees of freedom caused by the unique micropore environments, are shown to result in changes to phase behaviour. This work provides a general strategy for further manipulation of the H2 phase diagram via nanoconfinement effects, and for tuning of anisotropic potential through control of confining material composition and pore size. This approach could potentially provide lower energy routes to the formation and study of more exotic non-equilibrium condensed phases of hydrogen that could be useful for a wide range of energy applications.